Capacity gaps in post disaster construction & demolition waste management. Issue 4 (20th July 2015) - Karunasena, Gayani; Amaratunga, Dilanthi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to focus on the identification of the existing capacities of post disaster C & D waste management in developing countries, with a special emphasis on Sri Lanka to determine the capacity gaps and related influencing factors. Design/methodology/approach – Multiple case studies and expert interviews were conducted to gather primary information on the existing capacities of disaster C & D waste management. Three case studies, including 15 individuals and six experts representing government, non-government institutions and others, were selected. Findings – The results revealed the existing capacities, capacity gaps and influencing factors for post disaster C & D waste management in the areas of skills and confidence building, links and collaborations, continuity and sustainability, research and development, communication and coordination, organisational implementation and investment in infrastructure. Research limitations/implications – This study limited disaster C & D waste to debris generated from totally or partially damaged buildings and infrastructure as a direct impact of natural disasters or from demolished buildings and infrastructure at rehabilitation or at early recovery stages. Originality/value – The research enabled an analysis of existing capacities and identified capacity gaps in post disaster C & D waste management with influencing factors developing countries.